Pengaruh Metode Pemberian Tugas Dan Motivasi Belajar Terhadap Hasil Belajar Siswa Kelas X Smk Negeri 1 Percut Sei Tuan - Fauzia Khoirunnisa; Dhea Annisa Siregar; Fresty Flora Simanjuntak; Maria Kristina (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This type of research is Associative Quantitative which aims to determine the influence of assignment method and motivation variables on improving student learning outcomes, both partially and simultaneously. The population of this study were all class The results of this research show that the assignment method has a significant effect on student learning outcomes. The test used obtained the analysis results of R = 0.717 and F hit (F change) = 29.673 with p-value = 0.000 < 0.05. The learning motivation variable partially has a significant effect on learning outcomes with the analysis results R = 0.855 and F hit (F change) = 75.909 with p-value = 0.000 < 0.05. Simultaneously, the assignment method and learning motivation influence the learning outcomes of class The percentage of influence is 75.2%. These results also explain that the higher the assignment method and learning motivation, the greater the student learning outcomes and vice versa.